2005
DOI: 10.1158/1078-0432.ccr-05-0852
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic Instability and Cancer Invasion

Abstract: Purpose: A solidt umor embedded in host tissue is a three-dimensional arrangement of cells and extracellular matrix that acts as a sink of oxygen andce ll nutrients, thus establishing diffusional gradients. This and variations in vascular density and blood flow typically produce intratumoral regions of hypoxia andac idosis, and may result in spatially heterogeneous cell proliferation and migration.Here,we formulate the hypothesis that through thesemechanisms,microenvironmental substrate gradients may drive mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
160
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 148 publications
(195 citation statements)
references
References 48 publications
33
160
0
2
Order By: Relevance
“…This can negate the positive effects of anti-angiogenic therapy and lead to recurrence and metastasis. This result is consistent with the findings of [55], who suggested that combining anti-angiogenic therapy with adhesion therapy may counteract the negative problems associated with tumor fragmentation in the nutrient-poor regime.…”
Section: Fragmenting Growth Into Nutrient-poor Microenvironmentssupporting
confidence: 92%
See 4 more Smart Citations
“…This can negate the positive effects of anti-angiogenic therapy and lead to recurrence and metastasis. This result is consistent with the findings of [55], who suggested that combining anti-angiogenic therapy with adhesion therapy may counteract the negative problems associated with tumor fragmentation in the nutrient-poor regime.…”
Section: Fragmenting Growth Into Nutrient-poor Microenvironmentssupporting
confidence: 92%
“…Conversely, we found that increasing nutrient levels leads to greater morphological stability and increased tumor compactness, thereby rendering some tumors more resectable. These results support the contention [55] that treatments that seek to normalize tumor vasculature (by selectively "pruning" weak blood vessels with targeted anti-angiogenic therapy) may stabilize tumor morphology by providing increased access to nutrient. Since such treatments may also increase the accessibility to chemotherapeutic agents [105,188], our results provide additional support for the use of targeted anti-angiogenic therapy as adjuvant to chemotherapy and resection.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations